PELAPORAN KEUANGAN DIGITAL UMKM: APLIKASI SI APIK PADA SENTRA TAPE KUNING - Sayekti, Yosefa; Agustini, Aisa Tri; Irmadariyani, Ririn; Purnamawati, Indah; Irawan, Bambang; Prayitno, Agung; Adhani, Karenina Dwi; Agustin, Dania Safira (Jurnal Abdi Insani, 2024)
The progress of an MSME involves several factors, such as financial management and product marketing. One of the important aspects of financial reports for MSMEs is acquiring capital from external parties or banks. In line with the business activities conducted, MSME tape producers in Tegalwaru Village face challenges, specifically the absence of proper financial records due to a lack of financial literacy. In this service initiative, education was provided to Sentra Tape MSME business owners regarding the significance of preparing financial reports and the utilization of the financial information recording application (SI APIK). The objective of this activity is to enable Sentra Tape MSME business actors to independently record and prepare financial reports using the SI APIK application, accessible via mobile phones. Digital-based financial management can assist MSMEs in recording transactions, generating outputs in the form of useful financial reports not only for MSMEs but also for banks analyzing the suitability of prospective MSME debtors. The methods employed in this service include observation, introduction, and mentoring stages, financial report preparation, training, implementation, as well as monitoring and evaluation. The results attained through community service activities are documented in a report on the implementation stage, encompassing initial visits, preparations for Focus Group Discussions (FGD), and the actual FGD sessions. For future development plans, continuous Human Resources training is essential to support MSMEs in implementing SI APIK.